Medical Qigong: Fact or Fiction? Chinese Medical Qigong edited by Tianjun Liu and Kevin W. Chen - Cohen, Kenneth (Journal of Scientific Exploration, 2014)
Qigong, China’s ancient system of exercise, meditation, and energy therapy (“External Qi”),1 is, by sheer numbers, the most popular form of Complementary and Alternative Medicine (CAM) in the world. There are at least 100 million practitioners in China and millions worldwide, including more than 625,000 in the United States (NIH 2008). If we include Tai Chi, which is both Qigong and a martial art, there are an additional 2.2 million practitioners in the U.S. alone, and these numbers are increasing. One no longer needs to go to “New Age” or “Pseudo-science” sources to find healing reports. Rather, typical of readily available literature is the meta-analysis published by the American Medical Association in 2004, in which data indicated benefits in “balance and strength, cardiovascular and respiratory function, flexibility, immune system, symptoms of arthritis, muscular strength, and psychological effects” (Wang, Collet, & Lau 2004), though it is difficult to draw firm conclusions because of limitations or biases in some of the studies. More recent reports include impressive evidence of Qigong or closely related mind–body disciplines preventing oxidative stress and enhancing positive genetic expression (Dusek et al. 2008) as well as significant corroborating evidence for benefits previously reported (Jahnke et al. 2010).